Cross-platform development for microcontrollers: design of a virtual machine based portable programming language - Nuru Dashdamirli (Збірник наукових праць Державного університету інфраструктури та технологій: серія "Транспортні системи і технології", 2025)
The fundamental role of microcontrollers in embedded systems and the Internet of Things (IoT) environments necessitates efficient software development approaches. Resource limitations of microcontrollers, the complexity of low-level programming languages, and the challenges of implementing multitasking slow down the development process considerably. Additionally, the diversity of the microcontroller landscape creates substantial barriers to code portability, leading to increased development time to support different hardware platforms. This paper presents the design of a virtual machine-based programming approach to enable cross-platform development for microcontrollers. The proposed portable programming language integrates with a custom virtual machine, Mico8-Chip, to suit modern microcontroller applications. This allows intuitive control over peripherals and built-in support for concurrent execution. The provided abstraction layer significantly improves code portability and accelerates development by isolating application logic from underlying hardware specifics. The primary purpose of this work is to address the fragmented microcontroller ecosystem and the challenges of low-level programming by introducing a unified and portable development solution.